The immunopathogenesis of cryptococcal immune reconstitution inflammatory syndrome: understanding a conundrum. Issue 1 (February 2016) - Meya, David B.; Manabe, Yukari C.; Boulware, David R.; Janoff, Edward N.
Abstract : Purpose of review: Cryptococcal meningitis causes significant mortality among HIV-infected patients, despite antifungal therapy and use of antiretroviral therapy (ART). In patients with cryptococcal meningitis, ART is often complicated by immune reconstitution inflammatory syndrome (IRIS), manifesting as unmasking of previously unrecognized subclinical infection (unmasking CM-IRIS) or paradoxical worsening of symptoms in the central nervous system after prior improvement with antifungal therapy (paradoxical CM-IRIS). We review our current understanding of the pathogenesis of this phenomenon, focusing on unifying innate and adaptive immune mechanisms leading to the development of this often fatal syndrome. Recent findings: We propose that HIV-associated CD4 + T-cell depletion, chemokine-driven trafficking of monocytes into cerebrospinal fluid in response to cryptococcal meningitis, and poor localized innate cytokine responses lead to inadequate cryptococcal killing and clearance of the fungus. Subsequent ART-associated recovery of T-cell signaling and restored cytokine responses, characterized by IFN-γ production, triggers an inflammatory response. The inflammatory response triggered by ART is dysregulated because of impaired homeostatic and regulatory mechanisms, culminating in the development of CM-IRIS. Summary: Despite our incomplete understanding of the immunopathogenesis of CM-IRIS, emerging data exploring innate and adaptive immune responses could be exploited to predict, prevent and manage CM-IRIS and associated morbid consequences. Abstract : Supplemental Digital Content is available in the text